Kadar Transforming Growth Factor- Serum Berkorelasi Positif dengan Kadar Immunoglobulin M Anti-Phenolic Glycolipid-1 pada Narakontak Serumah Pasien Kusta Multibasiler - Primasari, Putu Yunita; Rusyati, Luh Made Mas; Karmila, I Gusti Ayu Agung Dwi; Winaya, Ketut Kwartantaya; Suryawati, Nyoman; Karna, Ni Luh Putu Ratih Vibriyanti (Fakultas Kedokteran Universitas Trisakti, 2023)
Background Leprosy is a chronic progressive infectious disease. Phenolic glycolipid-1 (PGL-1) is an antigen of Mycobacterium leprae, which can trigger the host’s antibody response. Transforming growth factorβ (TGF-β) plays an immunosuppressive role when the host is exposed to PGL-1 antigen or other M. leprae antigens. This study aims to determine the correlation of TGF-β levels with IgM anti-PGL-1 levels in patients with multibacillary leprosy household contacts. Methods Observational analytical study with a cross-sectional approach. The study subjects consisted of 48 household contact subjects and 24 non-household contact subjects aged 15-65 years old who were selected by consecutive sampling based on inclusion and exclusion criteria. 3 mL of venous blood samples were taken and then examined for IgM anti-PGL-1 and TGF-β with the ELISA kit. Data analysis was carried out using SPSS version 23, and a p-value <0.05 was significant. Results The mean level of IgM anti-PGL-1 in the household contact group was 685.46 ± 290.79 u/mL, while in the non-household contact group was 345.50 ± 206.58 u/mL. The mean TGF-β level in household contact groups was 256.69 ± 127.41 pg/mL, while in the non-household contact group was 144.85 ± 36.73 pg/mL (p<0.001). This study found a moderate positive relationship (r=0.450, p<0.001) between levels of TGF-β and IgM anti-PGL-1 household contacts and non-household contacts group. Conclusions The mean level of IgM anti-PGL-1 and TGF-β in household contacts is higher than in non-household contacts, with a significant difference. There is a moderate positive significant relationship between levels of TGF-β and IgM anti-PGL-1 household contacts and non-household contacts group.